2021
DOI: 10.1038/s41598-021-86852-5
|View full text |Cite
|
Sign up to set email alerts
|

Multisubstituted pyrimidines effectively inhibit bacterial growth and biofilm formation of Staphylococcus aureus

Abstract: Biofilms are multicellular communities of microorganisms that generally attach to surfaces in a self-produced matrix. Unlike planktonic cells, biofilms can withstand conventional antibiotics, causing significant challenges in the healthcare system. Currently, new chemical entities are urgently needed to develop novel anti-biofilm agents. In this study, we designed and synthesized a set of 2,4,5,6-tetrasubstituted pyrimidines and assessed their antibacterial activity against planktonic cells and biofilms formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…34 Moreover, the XRD patterns suggested a crystalline phase (Figure S1C). As shown in Figure S2, 1 To measure the antibacterial activity of the quaternary phosphorus salts, four bacterial strains (S. aureus, MRSA, E. coli, and P. aeruginosa) were treated with the salts and their inhibition zone and MIC were evaluated. The agar diffusion assay showed that PA is insensitive to (1,2-DBTPP)Br 2 , (1,4-DBTPP)Br 2 , and (1,6-DBTPP)Br 2 ; however, the presence of a clear zone surrounding the well appeared where these three materials were introduced (Figure S3).…”
Section: Characterization Of the Developed Quaternary Phosphorus Saltsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Moreover, the XRD patterns suggested a crystalline phase (Figure S1C). As shown in Figure S2, 1 To measure the antibacterial activity of the quaternary phosphorus salts, four bacterial strains (S. aureus, MRSA, E. coli, and P. aeruginosa) were treated with the salts and their inhibition zone and MIC were evaluated. The agar diffusion assay showed that PA is insensitive to (1,2-DBTPP)Br 2 , (1,4-DBTPP)Br 2 , and (1,6-DBTPP)Br 2 ; however, the presence of a clear zone surrounding the well appeared where these three materials were introduced (Figure S3).…”
Section: Characterization Of the Developed Quaternary Phosphorus Saltsmentioning
confidence: 99%
“…(1,4-DBTPP)Br 2 showed better antimicrobial efficiency against MRSA than (1,2-DBTPP)Br 2 and (1,6-DBTPP)Br 2 . Therefore, we focused on the antibacterial effect of only (1,4-DBTPP)Br 2 against MRSA in subsequent experiments.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Bacterial biofilms are highly tolerant to host immune system and can be up to 1,000 times less sensitive to antibiotic treatment than bacteria in planktonic/single cell state ( Kumar et al, 2017 ). Therefore, it is necessary to find agents that are not only active against planktonic cells, but also able to act on biofilms, either by preventing their formation or by disrupting them ( Hansa et al, 2021 ; Provenzani et al, 2021 ). However, conventional discovery of antibiotics is a long and expensive process, with a low success rate, and has not been able to cope with the emergence of antibiotic resistance and tolerance ( Payne et al, 2007 ; Ribeiro da Cunha et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…23 On the other hand, pyrimidine nitrogen-containing heterocyclic compounds are of great significance as they are abundant in nature and a wide spectrum of biological activities exhibited by the synthetic/semisynthetic derivatives. 24,25 Pyrimidine derivatives have shown a wide spectrum of biological activities such as antifungal (f-h), [24][25][26][27] antibiofilm (f-h), 25,26 antibacterial (a-e), 27 antiviral (j-k) 28 and anticancer (l-m). 29 Fig.…”
Section: Introductionmentioning
confidence: 99%